Penegakan Hukum Tindak Pidana Gratifikasi Yang Dilakukan Oleh Pegawai Imigrasi - Nadila Sekar Ayu; Subekti Subekti; Ernu Widodo (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This research aims to analyze the regulation and law enforcement of gratification offenses committed by immigration officers as state administrators within the framework of Indonesian anti-corruption law. Gratification is regulated under Article 12B of Law Number 31 of 1999 as amended by Law Number 20 of 2001 and is constructed as a formal offense, meaning that receiving gratification related to one’s official position and contrary to official duties constitutes a criminal act without requiring proof of state financial loss. This study employs normative legal research using statute and conceptual approaches. The legal materials consist of primary, secondary, and tertiary sources analyzed qualitatively. The findings indicate that the regulation of gratification provides a clear legal basis for holding immigration officers criminally liable. However, challenges remain in interpreting elements such as “related to official position” and “contrary to official duties,” as well as in the reporting mechanism. Therefore, consistent enforcement and comprehensive normative understanding are necessary to ensure legal certainty and integrity in public administration.